Identification of Criteria for Evaluating the Location of Youth Recreation and Leisure Centers - Rzeszowska, Natalia; Jasiak, Adriana (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Mental comfort for any individual is an important factor on the way to achieving one`s goals and objectives. Based on research focused on young people, and conducted in relation to the COVID-19 pandemic, physical activity positively affects mental comfort and is one of the social preventive measures for maintaining mental comfort. Thus, designing spaces dedicated to young people has become a common social interest. The purpose of the article was to identify criteria for locating recreational and leisure centers for young people.
Keywords: architecture; building; healing; location criteria; site selection; urban planning; youth; recreation; leisure